Localization of vasoactive intestinal polypeptide-receptor-immunoreactivity in human salivary glands - Herbst, Wolfgang Matthias; Kummer, Wolfgang; Heym, Christine (Neuropeptides, 1992)
A monoclonal VIP-receptor antibody derived from a human adenocarcinoma cell line (HT 29) was used in combination with immunogold silver staining for the immunohistochemical demonstration of VIP-receptor (rec) immunoreactivity (IR) in paraffin-embedded human salivary glands (parotid, palatal, labial glands). VIP-rec-IR was localized to mucous endpieces of labial and—to a lesser extent—palatal glands, intercalated ducts of the parotid gland, and excretory ducts of all glands investigated. The findings correlate well with known effects of VIP on mucous release and electrolyte transport in salivary glands. Lack of VIP-rec-IR at serous acini may point to immunologically different receptor subtypes in these glands.
Elektronische Reproduktion der Druck-Ausgabe 27. April 2004
Gesehen am 10.11.2025